Brain Tumour Segmentation using Level Set Method and Affected Area Calculation - Ahmed, Md. Manik; Hossain, Md. Imran (Engineering International, 2015)
Medical image processing is the most important and challenging field now days. MRI image processing is one of the parts of this field. Brain tumour segmentation in magnetic resonance imaging (MRI) has become an emergent research area in the field of medical imaging system. In this paper we proposed a variational level set method and some morphological operation to segment the brain tumour from MRI image by using MATLAB. Actually we describe variational formulation on geometric active contours that forces the level set function at zero level to be close to signed distance function and without re-initialization process. The variational formulation uses energy function and partial diferential equation to evolve the level set function. Tumour shape area is connected component in binary image and calculated this connected area using some properties of morphological operation.